TIDILAP: Treatment of iron deficiency in lipoprotein apheresis patients – A prospective observational multi-center cohort study comparing efficacy, safety and tolerability of ferric gluconate with ferric carboxymaltose. (May 2015) - Schatz, U.; Illigens, B.M.W.; Siepmann, T.; Arneth, B.; Siegert, G.; Siegels, D.; Heigl, F.; Hettich, R.; Ramlow, W.; Prophet, H.; Bornstein, S.R.; Julius, U.
Abstract: Objectives: Iron deficiency (ID) and iron deficiency anemia (IDA) are common findings in patients undergoing lipoprotein apheresis (LA). Different intravenous (iv) formulations are used to treat ID in LA patients, however guidelines and data on ID/IDA management in LA patients are lacking. We therefore performed a prospective observational multi-center cohort study of ID/IDA in LA patients, comparing two approved i.v. iron formulations, ferric gluconate (FG) and ferric carboxymaltose (FCM) . Methods: Inclusion criteria were a) serum ferritin <100 μg/L or b) serum ferritin <300 μg/L and transferrin saturation <20%. Patients received either FG (62.5 mg weekly) or FCM (500 mg once in ID or up to 1000 mg if IDA was present) i.v. until iron deficiency was resolved. Efficacy and safety were determined by repeated laboratory and clinical assessment. Iron parameters pre and post apheresis were measured to better understand the pathogenesis of ID/IDA in LA patients. Results: 80% of LA patients treated at the three participating centers presented with ID/IDA; 129 patients were included in the study. Serum ferritin and transferrin levels were reduced following apheresis (by 18% (p < 0.0001) and by 13% (p < 0.0001) respectively). Both FG and FCM were effective and well tolerated in the treatment of ID/IDA in LA patients. FCM led to a quicker repletion of iron stores (p < 0.05), while improvement of ID/IDA symptoms was not different. Number and severity of adverse events did not differ between FG and FCM, no severe adverse events occurred. Conclusions: Our results suggest that FG and FCM are equally safe, well-tolerated and effective in treating ID/IDA in LA patients. These data form the basis for follow-up randomized controlled trials to establish clinical guidelines.